Analysis of Completely Prevaporized Spray Flames with Water/Octane Core/Shell Structured Droplets. (11th October 2015) - Hsuan, Chung-Yao; Hou, Shuhn-Shyurng; Lin, Ta-Hui
Abstract : A series of studies on laminar flame propagation in off-stoichiometric dilute sprays of monodispersed inert or fuel drops had been investigated by large activation energy asymptotics. The present study extends previous theoretical model to consider water/octane core/shell structured drops instead of single-phase drops. The core/shell structured drops are composed of core fluid (water) encased by a layer of shell fluid (n-octane). In this study, we only deal with the case that core/shell structured drops are vaporized completely just at flame location. Namely, the discussions of this paper are restricted to the completely prevaporized mode. By varying parameters of core water radius, core-to-shell ratio, the amount of liquid loading, and the stoichiometric ratio (lean or rich burning), we examine the gasification of core water and shell fuel of core/shell structured drops upstream of the bulk flame and its relation to the internal heat transfer. The effects of drop radius, core-to-shell ratio, liquid loading, and overall heat loss or gain on flame propagation flux are reported and discussed.